29 Association between Risk of Falling and History of a Previous Falls over Four Years' Annual Follow-up. (20th December 2019) - Tan, Guo Jeng; Mat, Sumaiyah; Tan, Maw Pin
Abstract: Introduction: Falls in older persons lead to psychological as well as physical effects resulting in loss of quality of life, functional impairment and institutionalization. Previous studies have established falls in the previous 12 months as a risk factor for subsequent falls, but few have evaluated sequentially. This study aims to determine the sequential trend of 12-month retrospective fall recall over a four-year follow-up period. Methods: The Promoting Independence in our Seniors with Arthritis (PISA) study recruited individuals aged >=60 years followed up over four year. Participants were asked about presence of any fall in the preceding 12 months during each annual visit. Assessment performed during each visit included weight and the Knee Injury and Osteoarthritis Outcome Score (KOOS), hand grip strength, timed-up-and-go test, functional reach and Hospital Anxiety and Depression Scale. Results: Falls data were available for 218, 156, 117 and 100 individuals with 22.5%, 23.1%, 24.7% and 29.3% reporting falls at the first, second, third and fourth visits respectively. The mean age (standard deviation) at recruitment was 66.9 (7.1) years and 166 (74.1%) were women. The odds ratio (OR) (95% confidence interval, CI) for falls in the first, second and third years for fallers at recruitment were 2.45 (1.07-5.59), 3.55 (1.49-8.84) and 1.14 (0.43-3.05) respectively. Fallers at the second follow-up, were more likely to falls during second [OR (95%CI) = 2.41(1.94-12.90)] and third years [5.20 (1.91-14.13)]. Faller at the third visit for falls were more likely to fall in the third yaer [OR (95%CI) = 3.88(1.55-9.69)]. Conclusion: Falls in the preceding 12 months was associated with increased risk of falls in the subsequent two years. Faller at recruitment, however. were no longer at increased risk of falls at the third year of follow-up. This has implications for resource planning in terms to determine whether intervention is still useful with long waiting lists in overcrowded public health facilities.